Incarnation as a Sign of Divine Solidarity: A Theology of the Council of Nicaea - Ishak Servianto (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
The Council of Nicaea (325 AD) was an important milestone in the history of Christianity that affirmed the divinity of Christ through the formulation of homoousios, namely the essential equality between Jesus Christ and the Father. In the Western theological tradition, this decision is often understood in the context of the theology of its time. However, in the perspective of Minjung theology that developed in the context of the struggle of the oppressed people in Korea, the incarnation of Christ is not merely an ontological issue, but also an act of divine solidarity with the oppressed. This study interprets the decision of the Council of Nicaea in the framework of Minjung theology, emphasizing how the incarnation of Christ can be seen as God's act that radically sides with those who suffer. This study uses a hermeneutic approach and explores how the concept of homoousios can be interpreted as a form of God's involvement in the reality of human suffering. Analysis of Minjung theological texts, especially the works of theologian Ahn Byung-Mu, is used to highlight the dimension of liberation in the event of the incarnation. The results of this study indicate that the meaning of the incarnation in the Minjung perspective emphasizes that God not only has compassion, but actively enters the history of human suffering, providing hope and transformative power for marginalized communities. Thus, the Minjung theological interpretation of the Council of Nicaea offers a more contextual and relevant understanding for Christian communities struggling in situations of injustice.